Efficient Catalysts In situ Generated from Zinc, Amide and Benzyl Bromide for Epoxide/CO2 Coupling Reaction at Atmospheric Pressure. Issue 6 (2nd January 2019) - Zhang, Shuai; Han, Feng; Yan, Shaorui; He, Mingyue; Miao, Chengxia; He, Liang‐Nian
Abstract : Herein, in situ generated efficient catalysts were designed for fixation of CO2 to cyclic carbonates under mild conditions. Zinc bromide and N, N‐dibenzyl‐N, N‐dimethylammonium bromide, being proved as active catalyst species, were in situ generated from cheap Zn powder, dimethyl formamide and benzyl bromide, and catalyzed the cycloaddition reaction of CO2 and various terminal epoxides in moderate to excellent yields at 80 °C and atmospheric pressure of CO2 . The protocol circumvents the preparation of active catalysts, simultaneously possesses good catalytic activity under mild conditions. Abstract : Active catalysts in situ generated from Zn powder, dimethyl formamide and benzyl bromide were designed for fixation of CO2 to cyclic carbonates at 80 °C and atmospheric pressure of CO2 . Zinc bromide and N, N‐dibenzyl‐N, N‐dimethylammonium bromide, being proved as active catalyst species, were in situ generated and immediately converted various terminal epoxides to the corresponding carbonates efficiently.